A smoothed particle hydrodynamics approach for numerical simulation of tube heat exchangers - Anna E. Korenchenko; Anton V. Sukhov (Российский технологический журнал, 2025)
Objectives. In the confined space of heat exchangers, heat transfer rate plays a key role. The cross-sectional shape of the tubes can affect the heat transfer characteristics. Although circular tubes are easier and less expensive to manufacture, heat transfer in heat exchangers with tubes of other cross-sections can take place at higher rates, thus providing economic advantages. This makes the mathematical modeling of hydrodynamics and heat exchange in a tube apparatus relevant and interesting both from the theoretical and applied point of view. The aim of this study is to determine the influence of the shape of the tube cross-section on the heat transfer intensity.Methods. Numerical investigations were carried out using smoothed particle hydrodynamics. The possibilities of the smoothed particle method for resolving industrial heat transfer problems were demonstrated.Results. Heat transfer intensity was analyzed for tubes of circular and rectangular cross-sections. In cases where the cross sections of tubes in the heat exchanger are elongated in a given direction, the influence of the tube position in relation to the oncoming flow was studied. This was performed either with the long side along the flow or across it. The influence of tube surface protrusions on heat exchange was investigated. The flow around tubes with different cross-sectional shapes was also analyzed. The features of the flow around the tubes were established, and the velocity and temperature fields in the heat exchanger volume were defined. The values of the dimensionless heat flux (Nusselt number) for each case were also found.Conclusions. The influence of finned tubes in the laminar flow regime of heated fluid through the bundle of heat transfer tubes is insignificant. The highest value of the heat flux was observed for tubes of rectangular cross section with the long side transverse to the flow, and the difference with the data obtained for standard round tubes was found to be more than 15%.